Entrepreneurship Education in South Africa's Higher Education Institutions:Iin Pursuit of Promoting Self-Reliance in Students - Oluwatoyin Ayodele Ajani (International School for Social and Business Studies, 2024)
Purpose: Entrepreneurship Education (EE) has garnered increased attention in South African higher education institutions due to its potential to foster self-reliance and job creation in a country grappling with high unemployment rates. This study examines entrepreneurship education's role in promoting economic development and poverty alleviation in South Africa. Study design/methodology/approach: The study adopts a systematic review approach to explore the effectiveness of entrepreneurship education in addressing unemployment, creating employment opportunities, and fostering economic growth in South Africa. The study seeks to identify key findings and insights regarding integrating entrepreneurship education into teaching and learning practices in higher education institutions by synthesising existing literature. Findings: The findings indicate that entrepreneurship education has the potential to accelerate economic growth, reduce unemployment rates, and alleviate poverty traps in South Africa. By equipping students with entrepreneurial skills and mindset, entrepreneurship education can empower individuals to establish and sustain small businesses, thus contributing to economic development and poverty reduction. Originality/value: This study contributes to the existing literature by providing insights into the role of entrepreneurship education in addressing socio-economic challenges in South Africa. The findings underscore the importance of integrating entrepreneurship education into teaching and learning practices across all higher education institutions to tackle unemployment and poverty in the country effectively. The study emphasises the need for concerted efforts from stakeholders in higher education to prioritise entrepreneurship education to foster economic resilience and social upliftment in South Africa.